The Role of Guidance and Counseling Teachers in Implementing Responsive Services in Junior High Schools - Erik Farhan Syah; Sri Liana Ali; Bakhrudin All Habsy (Academia Edu Cendekia Indonesia (AEDUCIA), 2025)
Background: Guidance and counseling services are essential tools for students in overcoming various problems that may hinder their developmental tasks. These services play a significant role in helping students navigate personal, social, academic, and career challenges. Objective: This study aims to examine the concept, forms, and implementation of responsive services within the educational context. Method: The research method used is a systematic literature review, which analyzes various relevant journals and literature to gain a comprehensive understanding of responsive services in education. Result: The study findings indicate that responsive services can be implemented through individual counseling, consultations, case conferences, collaboration with relevant parties, and referrals to more competent experts as per the students' needs. Conclusion: This study concludes that responsive services play a crucial role in helping students overcome personal, social, academic, and career-related issues, thereby supporting their optimal development. Contribution: The contribution of this article is to provide a theoretical mapping of the forms of responsive services and their implications for the practice of guidance and counseling in schools.